Association Between Restless Legs Syndrome and Quality of Life Indicators Among Elderly - Filyandini, Savina; Marta, Ollyvia Freeska Dwi; Mashfufa, Erma Wahyu; Aini, Nur; Ariani, Tutu April (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Restless Legs Syndrome (RLS) is a common but often undiagnosed neurological disorder, characterized by an urge to move the legs accompanied by uncomfortable sensations, especially during rest at night. This condition is common in the elderly, disrupts sleep, and negatively impacts mood, energy, and quality of life, especially in nursing home residents. This study investigated the relationship between Restless Legs Syndrome (RLS) and quality of life in the elderly living in nursing homes. The research design was cross-sectional, with a consecutive sampling technique. The independent variable in this study was the severity of RLS measured using the IRLSSG questionnaire. Higher scores of IRLSSG and SF-36 indicated severe RLS and better QoL. Data analysis was conducted using the Spearman correlation test to assess the relationship between RLS and quality of life. The sample used in this study was 70 participants, calculated using G power software. The results showed that the average age of the participants was 75.41 years, with the majority of participants being women. Most participants experience mild RLS (67.14%). Statistical tests showed a significant negative association between RLS and QoL, specifically in the bodily pain (BP) domain, with a p-value of 0.04 and r= - 0.2465, which means increasing RLS will increase BP. Participants experienced mild pain, while 24.29% reported moderate pain, and 8.57% experienced severe pain. Statistical tests showed p value of 0.05, which indicates a significant relationship between the severity of RLS and quality of life. RLS has a significant impact on the quality of life in the elderly. Therefore, healthcare providers need to recognize and manage RLS symptoms to improve the overall well-being of this population. For further research, researchers need to consider additional factors such as comorbidities and social support, and implement interventions to reduce RLS symptoms.